(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
The relevance of the problem of formation and development of managerial competence of future police officers who are representatives of risky professions is substantiated. The expediency of introducing interactive technologies, in particular quest technologies, in the process of professional training of future police officers in order to form managerial competence is substantiated. Definitions of the terms "management competence", "quest-technology", "educational quest", "police quest" are given. Managerial competence is an integrative quality of a person and includes certain knowledge, abilities, skills and personal qualities that ensure the competent performance of managerial functions. The formation of managerial competence as a professionally significant personality quality of the future police officer requires the formation of certain knowledge, abilities and skills, as well as certain personality qualities that are components of managerial competence. The formation of management skills, skills and personal qualities is facilitated by the cadets’ performance of special exercises and tasks, which in terms of content and conditions are close to real situations of the professional activity of a police officer. One of the promising and effective methods of assimilating managerial knowledge and the formation of managerial abilities, skills and personal qualities are trainings with elements of quest technologies and practical classes in the form of a "police quest". The content of the stages of preparation and execution of the quest as an educational game is revealed. The expediency of using the "police quest" in the process of professional training of future police officers with the aim of forming their managerial competence has been substantiated and experimentally proven. A statistically probable presence of positive dynamics according to most indicators in the experimental groups after studying a special course, writing term papers and creative works, participating in training with elements of quest technologies and practical classes in the form of a "police quest" was revealed.